Endosymbiotic flexibility associates with environmental sensitivity in scleractinian corals - Putnam, Hollie M. (The Royal Society, 2012)
Flexibility in biological systems is seen as an important driver of macro-ecosystem function and stability. Spatially constrained endosymbiotic settings, however, are less studied, although environmental thresholds of symbiotic corals are linked to the function of their endosymbiotic dinoflagellate communities. Symbiotic flexibility is a hypothesized mechanism that corals may exploit to adapt to climate change. This study explores the flexibility of the coral–Symbiodinium symbiosis through quantification of Symbiodinium ITS2 sequence assemblages in a range of coral species and genera. Sequence assemblages are expressed as an index of flexibility incorporating phylogenetic divergence and relative abundance of Symbiodinium sequences recovered from the host. This comparative analysis reveals profound differences in the flexibility of corals for Symbiodinium, thereby classifying corals as generalists or specifists. Generalists such as Acropora and Pocillopora exhibit high intra- and inter-species flexibility in their Symbiodinium assemblages and are some of the most environmentally sensitive corals. Conversely, specifists such as massive Porites colonies exhibit low flexibility, harbour taxonomically narrow Symbiodinium assemblages, and are environmentally resistant corals. Collectively, these findings challenge the paradigm that symbiotic flexibility enhances holobiont resilience. This underscores the need for a deeper examination of the extent and duration of the functional benefits associated with endosymbiotic diversity and flexibility under environmental stress.